KINERJA KEUANGAN BIDDER FIRM SEBELUM DAN SESUDAH PENGGABUNGAN USAHA - Agung Mahadewi, Anak Agung Istri; Sudana, I Putu (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
Business combination is union of companies into one economic entity to gain control over the assets and operations of another company. Providing empirical evidence about the financial performance pre and post business combination on LQ-45 and Non LQ-45 companies is the aim of this study. The samples used are 27 go public companies that listed in Indonesia Stock Exchange by purposive sampling method. Documentation is the method used for collecting data. The analysis technique used is Wilcoxon Signed Rank and Mann-Whitney. It is found that there are differences in financial performance pre and post business combination on LQ-45 that showed in Total Asset Turnover. There are differences on Non LQ-45 that showed in Operating Cash Flow Per Asset. The difference between the company's financial performance on LQ-45 and Non LQ-45 is showed on Return on Equity, Return on Capital Employed, Net Profit Margin, Operating Profit Margin, and Total Asset Turnover.
Keywords: business combination, financial performance, bidder firm